PENINGKATAN KEMAMPUAN BERBAHASA LISAN MELALUI METODE BERCAKAP-CAKAP PADA ANAK DI TK BINA INSAN - Putri, Deasyana; Fadillah, Fadillah; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe arm of this research was to improved verbal language skills though conversational method in 4-5 years old children at TK Bina Insan, Southeastern Pontianak. The research method is used a descriptive method with classroom action research consisted of implementation, observation and reflection. Data collected through observation, interview and documentation. Based on the result of data anlysis, in general it can be concluded that verbal language skills through conversational methods in grup A 4-5 years old children at TK Bina Insan, Southeastern Pontianak. In particular it can be concluded that; (1). The planned of learning to improved verbal language skills though conversational method of conversed is catagorized very well; (2). The implementation of learning to improved verbal language skills through conversational method of conversed is catagorized very well, that means the implementation of verbal language skills learning has been carried out in accordance with the made plans of learning; (3). The results of increased learning of verbal language skills through the method is good, because every aspect of children?s verbal language skills has increased with very high catagories. Keyword : Verbal Communication, Converse